Costs of Drug Therapy in Patients with Ankylosing Spondylitis in Brazil. Issue 2 (December 2016) - Machado, Marina; Ferre, Felipe; Moura, Cristiano; Almeida, Alessandra; Andrade, Eli; Cherchiglia, Mariângela; Acurcio, Francisco
Abstract Introduction The Brazilian Public Health System offers free-of-charge drug treatment for ankylosing spondylitis (AS) to all Brazilian citizens. We report here the first population-based cohort study on patients with AS in Brazil. The aim of this study was to evaluate the costs of the tumour necrosis factor (anti-TNF) blockers and disease-modifying antirheumatic drugs (DMARDs) that were used in the treatments of patients with AS in Brazil between March 2010 and September 2013. Methods A retrospective cohort study was performed using administrative databases. All patients with a diagnosis of AS who were aged 18 years or older and had been dispensed anti-TNF or DMARDs were included in the analysis. The cost analysis was carried out from the health system perspective, and the results were described as median monthly cost per capita and the annual cost over the study period. Results A search of the databases identified 1251 patients with AS who were treated during the study period, of whom 63.3% were male; the median age was 41 years. During the study period, 78.0% of patients initiated treatment with anti-TNF drugs and 22.0% with DMARDs. The median monthly cost per capita was US$ 1650 for anti-TNF therapy and US$ 25 for treatment with DMARDs. Among the anti-TNF drugs, therapy with etanercept was associated with the lowest cost per patient, followed by adalimumab and infliximab. No difference in monthly cost was observed in relation to gender and age. Conclusion The cost per patient of treating AS in this study cohort was lower with etanercept than with adalimumab and infliximab. These results highlights the economic burden of treating patients with AS.